Effect of suction and blowing control on NACA 0012 airfoil at low Reynolds number. (July 2020) - Zhang, Zhiyong; Wang, Tuantuan; Wang, Yafei; Guo, Hao
Abstract: To control the separation of flow past an airfoil with a simple jet mechanism, based on the Large Eddy Simulation from Favre, a suction-blowing combined jet is studied with holes placed on a NACA0012 airfoil's upper surface and Re = 10 4 attack angle α = 6°. The results show the control mode of front-hole suction and back-hole blowing is effective. It can suppress the disturbance in the flow field and increase the lift-to-drag ratio of the airfoil at the same time.